2011
DOI: 10.4061/2011/142413
|View full text |Cite
|
Sign up to set email alerts
|

Transient Non-Autoimmune Hyperthyroidism of Early Pregnancy

Abstract: It is characterized by chemical and sometimes clinical hyperthyroidism, without evidence of thyroid autoimmunity that resolves spontaneously by 16 weeks gestation without significant obstetrical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 57 publications
0
50
0
12
Order By: Relevance
“…Case studies have indicated that, serum levels of hCG of >100,000 mIUL -1 are usually needed to produce clinical evidence of thyrotoxicosis [3]. Such high levels are seen in conditions like hyperplacentosis, hyperemesis gravidarum, gestational trophoblastic disease, multiple pregnancy and hyper reaction-luteinalis [7]. These conditions are associated with the clinical entity known as 'transient non autoimmune hyperthyroidism in early pregnancy' wherein hCG is the main mediator of hyperthyroidism [7].…”
Section: Relationship Between Hcg and Thyroidmentioning
confidence: 99%
See 4 more Smart Citations
“…Case studies have indicated that, serum levels of hCG of >100,000 mIUL -1 are usually needed to produce clinical evidence of thyrotoxicosis [3]. Such high levels are seen in conditions like hyperplacentosis, hyperemesis gravidarum, gestational trophoblastic disease, multiple pregnancy and hyper reaction-luteinalis [7]. These conditions are associated with the clinical entity known as 'transient non autoimmune hyperthyroidism in early pregnancy' wherein hCG is the main mediator of hyperthyroidism [7].…”
Section: Relationship Between Hcg and Thyroidmentioning
confidence: 99%
“…Such high levels are seen in conditions like hyperplacentosis, hyperemesis gravidarum, gestational trophoblastic disease, multiple pregnancy and hyper reaction-luteinalis [7]. These conditions are associated with the clinical entity known as 'transient non autoimmune hyperthyroidism in early pregnancy' wherein hCG is the main mediator of hyperthyroidism [7]. weeks gestation, changes in serum hCG and TSH are mirror images of each other, and there is a significant negative correlation between the individual TSH (nadir) and peak hCG levels.…”
Section: Relationship Between Hcg and Thyroidmentioning
confidence: 99%
See 3 more Smart Citations